Endometriosis – diagnosis and treatment according to current recommendations - Szyłło, Krzysztof; Górski, Jarosław (Menopause Review/Przegląd Menopauzalny, 2011)
Complex and not fully recognized etiopathogenesis of endometriosis results in the lack of effective diagnosis and treatment of the disease. Strong and persistent pain ailments in the abdomen, painful menstruation, dyspareunia as well as infertility worsen physical and psychological life standards. Lack of effective laboratory methods of recognizing endometriosis force more invasive, laparoscopic diagnostic methods. The method of treatment is mostly dependent on occurrence of pelvic pain or infertility connected with endometriosis. Authors make an attempt of systematizing main rules of recognizing and treatment of endometriosis on the basis of current recommendations of gynecological associations.